Cochlear Gene Therapy for Sensorineural Hearing Loss: Current Status and Major Remaining Hurdles for Translational Success - Zhang, Wenjuan; Kim, Sun Myoung; Wang, Wenwen; Cai, Cuiyuan; Feng, Yong; Kong, Weijia; Lin, Xi (Frontiers in Molecular Neuroscience, 2018)
Sensorineural hearing loss (SNHL) affects millions of people. Genetic mutations play a large and direct role in both congenital and late-onset cases of SNHL (e.g., age-dependent hearing loss (ADHL)). Although hearing aids can help moderate to severe hearing loss the only effective treatment for deaf patients is the cochlear implant (CI). Gene- and cell-based therapies potentially may preserve or restore hearing with more natural sound perception, since their theoretical frequency resolution power is much higher than that of cochlear implants. These biologically-based interventions also carry the potential to re-establish hearing without the need for implanting any prosthetic device; the convenience and lower financial burden afforded by such biologically-based interventions could potentially benefit far more SNHL patients. Recently major progress has been achieved in preclinical studies of cochlear gene therapy. This review critically evaluates recent advances in the preclinical trials of gene therapies for SNHL and the major remaining challenges for the development and eventual clinical translation of this novel therapy. The cochlea bears many similarities to the eye for translational studies of gene therapies. Experience gained in ocular gene therapy trials, many of which have advanced to clinical phase III, may provide valuable guidance in improving the chance of success for cochlear gene therapy in human trials. A discussion on potential implications of translational knowledge gleaned from large numbers of advanced clinical trials of ocular gene therapy is therefore included.